Hydrogen Production Combining Steam Reform and Electrolysis by Electrochemical Cell Using Proton Conducting Oxide. (10th July 2019) - Okuyama, Yuji; Nagatomo, Satoshi; Niisaka, Aoi; Matsunaga, Naoki; Sakai, Go; Sasamata, Yuichi; Ogura, Yusuke; Mizutani, Yasunobu
Abstract : Steam electrolysis using a proton conducting oxide might offer low-cost hydrogen production using a combination of electrical energy and thermal energy that comes from solar energy. On the other hand, the hydrogen production efficiency is low due to the electrical leakage for the electrolysis of H2 O-O2 . In this study, the additive effect of methane on the hydrogen production efficiency for stem electrolysis using a proton conducting oxide was examined. The steam electrolysis was performed under a H2 O-O2, H2 O-CH4 atmosphere at 1073 K. The hydrogen evolution rate of the H2 O-CH4 electrolysis with the Ru catalyst was in agreement with the value according to Faraday's law. The hydrogen evolution rate and the electrolysis voltage were found to increase in the order of the H2 O-CH4 electrolysis with the catalyst < the H2 O-CH4 electrolysis without the catalyst < the H2 O-O2 electrolysis.